An efficient hybrid numerical scheme for solvinggeneral second order initial value problems (IVPs) - Adeniran, Oluwadare; Ogundare, Babatunde (International Journal of Applied Mathematical Research, 2015)
The paper presents a one step hybrid numerical scheme with two off grid points for solving directly the general second order initial value problems of ordinary differential equations. The scheme is developed using collocation and interpolation technique. The proposed scheme is consistent, zero stable and of order four. This scheme can estimate the approximate solution at both step and off step points simultaneously by using variable step size. Numerical results are given to show the efficiency of the proposed scheme over the existing schemes.